(untitled) (Baghdad Science Journal, 2025)
Exposure assays to magnetized water have so far revealed striking results. The present study was conducted to determine the effects of magnetized water treatment with in different intensities 500 , 1000 and 1500 Gauss on some biological aspects for species of freshwater Gastropod Lymnaea lagotis (Schrank, 1803) which important species in faun of aquatic habitats of Iraq. This species are considered a component of the food chain. The obtained results compared with these species which lived in the river(control). Result of these experiments showed increased significance the shell size (shell high, shell aperture length, shell aperture width and shell width) for L. lagotis with increased intensity magnetized water such as treated water with 1000 Gauss intensity compared with untreated water. Although increase significant was observed to fecundity for snails such as (egg mass dimensions, number and diameter of eggs and survival juveniles) with increased intensity of magnetized water comparative with untreated water.